Penentuan Zonasi Bencana Tsunami di Kabupaten dan Kota Pesisir Provinsi Sumatera Barat - Tri Utami Vemileza Putri; Ira Kusuma Dewi; Lenny Marlinda (SPEJ (Science and Physic Education Journal), 2022)
Abstract: The purpose of this study was to determine how the tsunami disaster zoning in the Regency and Coastal City of West Sumatra Province was determined. The survey results show that geographically the regencies and cities on the coast of West Sumatra are around the threat of a tsunami, in addition to economic activities, government activities, and high population density around the coastal area. Regencies and cities located on the coast of West Sumatra, including West Pasaman Regency, Agam Regency, Padang Pariaman Regency, Pariaman City, Padang City, Pesisir Selatan Regency, and the Mentawai Islands, are feared to be the following places to be hit by a tsunami, for this reason, efforts are needed - efforts to overcome the tsunami hazard. In conclusion, the tsunami risk zone in the province of West Sumatra, which is very dangerous, is in the Mentawai archipelago with a wave height of 20-35 m and a wave arrival time of 10-20 minutes with a warning level of alert. And the story of tsunami disaster risk in coastal districts and cities of West Sumatra province is divided into four zones, namely: Not dangerous, Less dangerous, namely West Pasaman district, the danger is Agam district, Pariaman city, Padang Pariaman district, Padang city, and Pesisir Selatan district, Very dangerous namely the Mentawai Islands. Keywords: ArcGis 10.3, Comcot, Tsunami